2004
DOI: 10.1007/s00239-004-2666-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Molecular Evolutionary History of the Ascorbate Peroxidase Gene Family: Inferences from the Rice Genome

Abstract: Ascorbate peroxidase (APx) is a class I peroxidase that catalyzes the conversion of H(2)O(2) to H(2)O and O(2) using ascorbate as the specific electron donor. This enzyme has a key function in scavenging reactive oxygen species (ROS) and the protection against toxic effects of ROS in higher plants, algae, and Euglena. Here we report the identification of an APx multigene family in rice and propose a molecular evolutionary relationship between the diverse APx isoforms. In rice, the APx gene family has eight mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
170
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 39 publications
10
170
0
1
Order By: Relevance
“…This enzyme catalyzes the reduction of H 2 O 2 using ascorbate as the specific electron donor (Asada, 1992;Teixeira et al, 2004). In our study, treatment with cement dust enhanced APX activity in Arabidopsis plants.…”
Section: Discussionsupporting
confidence: 51%
“…This enzyme catalyzes the reduction of H 2 O 2 using ascorbate as the specific electron donor (Asada, 1992;Teixeira et al, 2004). In our study, treatment with cement dust enhanced APX activity in Arabidopsis plants.…”
Section: Discussionsupporting
confidence: 51%
“…5A), which is putatively localized in the thylakoid (Teixeira et al, 2004). Additionally, OsHTAS was simultaneously localized to the nucleus and cytoplasm (Fig.…”
Section: Discussion the Oshtas Gene Functions In Leaf Blade To Modulamentioning
confidence: 90%
“…Recent genome-wide analysis in higher plants indicated that APX belongs to a multigenic family, since there are nine genes in Arabidopsis, eight in rice, and seven in tomato. [43][44][45] These APX families are further classified into three subfamilies according to subcellular localization, viz., chloroplastic, cytosolic, and microbody isoenzymes. 5) Chloroplastic isoenzymes have stroma-soluble (sAPX) and thylakoid membranebound (tAPX) forms.…”
Section: Enzymatic and Molecular Properties Of Apx Isoenzymesmentioning
confidence: 99%